Identification of Functional Modules and Key Pathways Associated with Innervation in Graft Bone—CGRP Regulates the Differentiation of Bone Marrow Mesenchymal Stem Cells via p38 MAPK and Wnt6/β-Catenin - Ziqian Wu; Xudong Wang; Jingcun Shi; Anand Gupta; Yuhan Zhang; Bingqing Zhang; Yang Cao; Lei Wang (Stem Cells International)
Bone resorption occurs after bone grafting, however, contemporaneous reconstruction of the innervation of the bone graft is a potential treatment to maintain the bone mass of the graft. The innervation of bone is an emerging research topic. To understand the potential molecular mechanisms of bone innervation after bone grafting, we collected normal iliac bone tissue as well as bone grafts with or without innervation from nine patients 1 year after surgery and performed RNA sequencing. We identified differentially expressed genes) from these samples and used the gene ontology and Kyoto Encyclopedia of Genes and Genomes databases for functional enrichment and signaling pathway analysis. In parallel, we established protein–protein interaction networks to screen functional modules. Based on bioinformatic results, we validated in vitro the osteogenic differentiation potential of rat bone marrow mesenchymal stem cells (BMMSCs) after calcitonin gene-related peptide (CGRP) stimulation and the expression of p38 MAPK and Wnt6/β-catenin pathways during osteogenesis. Our transcriptome analysis of bone grafts reveals functional modules and signaling pathways of innervation which play a vital role in the structural and functional integration of the bone graft. Simultaneously, we demonstrate that CGRP regulates the differentiation of BMMSCs through p38 MAPK and Wnt6/β-catenin.